Determination of Trace Amount of Sodium Dodecyl Sulfate Surfactant by Extraction Spectrophotometric Method - ATTARAN, A.M.; IMAM, S.H.; PARHAM, H. (Asian Journal of Chemistry, 2010)
A simple, sensitive extraction-spectrophotometric method for determination of trace amounts of sodium dodecylsulfate (SDS) is reported. The (SDS––OTB+) ion-pair in buffered media is quantitatively extracted into dichloromethane and its absorbance is measured at 625 nm in room temperature. The effect of different variables such as solvent, volume of extractant, volume of cationic reagent, pH, shaking time is investigated and optimum conditions for quantitative extraction of sodium dodecylsulfate is obtained. Linear calibration curve over the sodium dodecylsulfate concentration range of 0.1-4.0 μg mL-1 and regression coefficient of 0.9996 is obtained. The relative standard deviation (RSD) of 7 replicate determinations of sodium dodecylsulfate concentrations of 0.2, 1.0 and 4.0 μg mL-1 is 3.75, 1.84 and 0.63 %, respectively. The detection limit of the method is 8.91 ng mL-1. The amount of sodium dodecylsulfate in Karoon river as real sample is determined by standard addition method which is 0.141 μg mL-1. The interference of 22 cationic and anionic species have also been evaluated and it was found that most species have no effect on the extraction selectivity. The method was applied to the Karoon river raw water contaminated with industrial and house sewage. The results showed high potential of the recommended method for the determination of sodium dodecylsulfate in water samples.